Kolaviron prevents ethylene glycol monoethyl ether-induced testicular apoptosis via down-regulation of stress proteins, Fas/Fas-L and caspases expressions in rats (2013)
This study investigated the protective role of kolaviron, a natural antioxidant biflavonoid isolated from the seed of Garcinia kola, in ethylene glycol monoethyl ether (EGEE)-induced testicular dysfunction in male rats. Adult male Wistar rats were exposed to EGEE (200 mg/kg) separately or in combination with either kolaviron (100 or 200 mg/kg) or vitamin E (50 mg/kg) for 14 days. Immunoblot analysis revealed that EGEE exposure alone significantly increased stress-inducible proteins levels. The increased protein expression of active caspases, Fas and Fas-L, was accompanied by nuclear factor kappa B downregulation and elevation of cytosolic cytochrome c level in EGEE-treated rats. In addition, the observation from immunofluorescence staining was consistent with the increased TUNEL-positive nuclei in the testes of EGEE-treated rats. Kolaviron and vitamin E significantly inhibited induction of stress proteins and germ cell apoptosis in EGEE-treated rats. Overall, kolaviron by virtue of its antioxidant and anti-apoptotic properties prevented EGEE-induced reproductive toxicity in rats.